Effects of Metabolizable Energy Intake and Body-Weight Restriction on Layer Pullets: 1-Growth, Uniformity, and Efficiency - Thiago L. Noetzold; Jo Ann Chew; Douglas R. Korver; René P. Kwakkel; Laura Star; Martin J. Zuidhof (Poultry, 2023)
This study aimed to determine the effects of dietary energy and body-weight (BW) restriction on layer pullets’ growth, uniformity, and feed efficiency. Two experiments were conducted using a precision feeding (PF) system (Experiment 1) and a conventional feeding (CON) system (Experiment 2). Experiment 1 consisted of a 2 × 4 factorial arrangement (eight treatments) with two feed allocation (FA) levels: meal every visit (MEV) or restricted to the lower boundary of Lohmann Brown-Lite pullets; and three dietary metabolizable energy (ME) levels: Low, Standard (Std), and High (2600, 2800, and 3000 kcal/kg, respectively); the fourth treatment enabled birds to choose from the three diets (Choice). Experiment 2 consisted of a 2 × 3 factorial arrangement (six treatments): two FA levels (ad libitum or restricted) and three dietary ME levels (Low, Std, and High). In each experiment, BW, coefficient of variation (CV), average daily feed intake (ADFI), average daily metabolizable energy intake (MEI), and feed conversion ratio (FCR) were recorded. Diet ADFI preferences and feeding motivation were determined only in the PF experiment. ANOVA was conducted on each experiment with the two main effects as fixed factors (FA and dietary ME), and age or period as the sources of variation. Differences were reported at p ≤ 0.05. MEV (PF experiment) and ad libitum-fed (CON experiment) pullets had greater BW compared to restricted-fed pullets (p < 0.05). The lowest CV was observed in the restricted-fed pullets from the PF experiment (p < 0.05). ADFI was greater in pullets fed the Low ME diet in the PF experiment compared to all the other groups, and the lower the dietary ME, the greater the ADFI in the CON experiment (p < 0.05). Choice-feeding pullets preferred feed with greater ME content in the PF experiment (p < 0.05). The lower the dietary ME, the greater the FCR in the CON experiment (p < 0.05). Restricted-fed pullets had greater daily visits, and lower daily meals, meal size, and successful visits to the PF system (p < 0.05). In conclusion, the results of this trial indicated that lower dietary ME increased FCR and ADFI, whereas feed restriction decreased BW and increased feeding motivation. Future steps after this trial will include examining the effects of dietary energy and feed restriction on carcass composition and sexual maturation.